Peculiarity of mathematical objects. Dimensional figures - Kavaliauskas, Algis (Lietuvos matematikos rinkinys, 2021)
The article deals with formulating of dimensional problems. It is shown what kind of difficulties arises when in one formula dimensional figures are used together with figures without any dimension. The problem of invariability of a formula in respect to change of dimension is introduced. Solutions of the problem are proposed.
Keywords: dimensional figure; dimensional variable; dimension; school mathematics